A review of social media methods and lessons learned from the National Children's Study. Issue 4 (15th November 2017) - Burke-Garcia, Amelia; Winseck, Kate; Jouvenal, Leslie Cooke; Hubble, David; Kulbicki, Kathryn M.
Abstract : Introduction: Given the reach and influence of social media, the National Children's Study Vanguard Study evaluated the feasibility, acceptability, and cost of using social media to support participant retention. Methods: We describe a social media experiment designed to assess the impact of social media on participant retention, discuss several key considerations for integrating social media into longitudinal research, and review factors that may influence engagement in research-related social media. Results: User participation varied but was most active when at launch. During the short life of the private online community, a total of 39 participants joined. General enthusiasm about the prospect of the online community was indicated. There were many lessons learned throughout the process in areas such as privacy, security, and Institutional Review Board clearance. These are described in detail. Conclusions: The opportunity to engage participants in longitudinal research using online social networks is enticing; however, more research is needed to consider the feasibility of their use in an ongoing manner. Recommendations are presented for future research seeking to use social media to improve retention in longitudinal research.